Thin wall injection‐overmoulding of polyamide 6/polypropylene multilayer parts: PA6/PP‐g‐ma interfacial adhesion investigations. Issue 17 (19th November 2020) - Lafranche, Eric; Macedo, Sandra; Ferreira, Pedro; Martins, Carla I.
Abstract: This work investigates the interfacial adhesion of PA6/PP‐g‐MA in a thin‐walled multilayer part obtained by injection overmoulding. This process is a good solution to the need of weight reduction for the sustainable and economic growth of food packaging. A rigid plastic food package is a complex multilayer structure obtained from the association of polymers with different properties to achieve good barrier, environment, or thermo‐mechanical performance. The present study aims to obtain a complete understanding of the interfacial adhesion of PA6/PP‐g‐MA interface in a three‐layer PA6/sealant/PP assembly through microscopy analysis, mechanical characterization, and inter‐diffusion models. Optical microscopy, XPS, and AFM analyses showed the presence of a copolymer interphase. This layer is greatly dependent on the holding pressure applied, which revealed to be the key parameter to obtain the best results in terms of failure strength. A better interface wettability improves the inter‐diffusion distance and thus chemical grafting efficiency. Other interface improvements were achieved by the addition of EVA in the PP‐g‐MA layer. The lowest viscosity of the EVA dispersed phase has led to a fully cohesive failure due to an interface diffusion efficiency. The presence of EVA increased more than 80% of the peeling performance of the assemblies. Abstract :